First record of Longibrachium atlanticum (Day, 1973) (Polychaeta, Onuphidae) in the Mediterranean Sea - Cantone, G.; Lanera, P.; Sordino, P. (Vie et Milieu, 1997)
The genus Longibrachium Paxton, 1986 (Polychaeta, Onuphidae), represented by the species L. atlanticum (Day 1973), is reported for the first time in the Mediterranean Sea. Morphologic differences with Atlantic specimens and the biogeographic implications of this record are discussed.
Kristian Fauchald's Polychaeta DB